2017
DOI: 10.5505/itujfa.2018.36002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing change in quality of life following rehousing from slum settlements to social housing

Abstract: This article is the result of a study which aimed to evaluate how a group of resettled residents have adapted to their new houses in Istanbul. The removal of squatter dwellers and their relocation to social housing units affect their quality of life after the removal. To assess the quality of life of residents who have now been living for a long time in social housing after their slums were demolished by the Istanbul Metropolitan Municipality, interviews were conducted with the aid of a questionnaire. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
1
4
0
6
Order By: Relevance
“…Results of the present study show that the social housing pattern is considered as the most suitable solution to the problem of the revival of urban WoUFs in developing countries, also because it perfectly fits the need of low-income people in developing countries; indeed, in social housing, rental rates are lower than the average rental rate in the housing market. This finding is in line with prior studies (Bodur & Yüksel, 2017;Grimshaw, 2019;Harputlugil et al, 2019;Laffin, 2019), which has shown that the social housing pattern is a housing pattern priority in both developed and developing countries, because it is helping the recovery of abandoned areas and giving them a renewed life. However, due to the fact that prior literature did not enlighten the discussion of how to sustainably recover WoUFs of cities in developing countries (Akbar Pour Saraskanroud et al, 2011;Amini et al, 2018;Gorjinia & Amini, 2016;Jaliz et al, 2020;Mosayyebzadeh et al, 2020;Samiei & Sayafzadeh, 2016;Sarvari et al, 2019), this study makes a strong theoretical advancement within the urban regeneration stream of study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of the present study show that the social housing pattern is considered as the most suitable solution to the problem of the revival of urban WoUFs in developing countries, also because it perfectly fits the need of low-income people in developing countries; indeed, in social housing, rental rates are lower than the average rental rate in the housing market. This finding is in line with prior studies (Bodur & Yüksel, 2017;Grimshaw, 2019;Harputlugil et al, 2019;Laffin, 2019), which has shown that the social housing pattern is a housing pattern priority in both developed and developing countries, because it is helping the recovery of abandoned areas and giving them a renewed life. However, due to the fact that prior literature did not enlighten the discussion of how to sustainably recover WoUFs of cities in developing countries (Akbar Pour Saraskanroud et al, 2011;Amini et al, 2018;Gorjinia & Amini, 2016;Jaliz et al, 2020;Mosayyebzadeh et al, 2020;Samiei & Sayafzadeh, 2016;Sarvari et al, 2019), this study makes a strong theoretical advancement within the urban regeneration stream of study.…”
Section: Discussionsupporting
confidence: 92%
“…In developed countries, such as Singapore, Germany, United Kingdom, United States, Denmark and France, the social housing model has been used as a top priority (Grimshaw, 2019;Laffin, 2019). In developing countries such as Malaysia, the government housing model has been used as the primary pattern (Bilal, Meera, & Razak, 2019), while Turkey has placed social housing as a top priority (Bodur & Yüksel, 2017;Harputlugil, Harputlugil, Pedergnana, & Sarıoglu, 2019).…”
Section: Identifying Patterns Of Urban Housing Development and Key Se...mentioning
confidence: 99%
“…They were occupied by manufacturing facilities and their workers, as Bağcılar was the county with mostly workers dwellings (Ocakçı, 2000), but then they turned into centres of sprawl in the 2000's (Akdogan, 2009). Later, it became a site for urban regeneration programs since 2011, thanks to the aforementioned legislation that promise urban aesthetic and durability against the threat of an earthquake (Bodur & Dülgeroğlu Yüksel, 2017;Karaman, 2009;Ozcevik et al, 2008;Yapıcı & Ileri, 2019). The reason why Başakşehir is among these counties is regarding its special case of transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In Istanbul, large areas that allow for the construction of gated communities with shopping malls have become much more common with the urbanisation policies of administrative bodies. Public lands are offered to private construction companies as a partnership deal with governmental agency of public housing, TOKI (Bodur & Dülgeroğlu Yüksel, 2017). In cities under intense urban transformation, the newly-built housing projects eventually see an overall increase in housing prices when social amenities become extensive (Montgomery, 2008;Tang, 2006).…”
mentioning
confidence: 99%
“…This can lead to conflicts between the slum dwellers and local authorities. Furthermore, several scholarly studies have contended that eviction and relocation activities are the main catalysts for the erosion of citizens' original sociocultural livelihoods and communal ties, e.g., [20][21][22][23]. In the academic realm, several scholars have conducted extensive research on slums in different settings, including slums in megacities such as Dharavi in Mumbai and Bangkok [24][25][26][27], deteriorated neighborhoods in Mauritius [28], slums situated in water bodies in Nigeria [29], and slums located along riversides in several locations in Indonesia [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%